Contemplation and social transformation: the example of Thomas Merton - P. Sheldrake (Acta Theologica)
This essay examines the relationship between the Christian tradition of contemplation and social action. It takes as its paradigm the life and writings of Thomas Merton (Fr Louis), an American Cistercian monk at the Abbey of Gethsemani, Kentucky, who became one of the most widely-read and influential spiritual writers as well as Christian social commentators of the mid-twentieth century. Merton, who often wrote through an autobiographical medium, gradually moved away from an early emphasis on contemplative withdrawal to a belief that the monastic life is a form of counter-cultural solidarity with those who struggle for social transformation and justice. The essay more broadly explores the theological basis for a coherence of mysticism and action in contrast to some misinterpretations of the Christian language of interiority. It concludes with an exploration of the relationship between contemplation and politics in a number of twentieth and twenty-first century theologians, both Catholic and Protestant.